2019
DOI: 10.1002/jcb.29040
|View full text |Cite
|
Sign up to set email alerts
|

Absent in melanoma 2 suppresses epithelial‐mesenchymal transition via Akt and inflammasome pathways in human colorectal cancer cells

Abstract: Absent in melanoma 2 (AIM2) is a critical component in natural immunity system and is closely related to cancer initiation and development. It has been shown that AIM2 inhibited colorectal cancer (CRC) development and cell proliferation. It remains unresolved how AIM2 acts on CRC metastasis. In this study, we assessed migration, invasion ability, and epithelial‐mesenchymal transition (EMT) program upon AIM2 overexpression or knockdown in human CRC cells. Transwell assay demonstrated that upregulation of AIM2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Previous study showed that Akt is a pivotal serine/threonine kinase and promotes epithelial‐mesenchymal transition process through NF‐κB and GSK‐3β in cell biological progression including cell proliferation, apoptosis and metabolism. AIM2 inflammasome activation impaired cell invasion and metastasis via inhibiting Akt pathway in colorectal cancer 33 . Furthermore, overexpression of AIM2 in human renal cancer suppressed cell metastasis via enhancing autophagy induction 21 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous study showed that Akt is a pivotal serine/threonine kinase and promotes epithelial‐mesenchymal transition process through NF‐κB and GSK‐3β in cell biological progression including cell proliferation, apoptosis and metabolism. AIM2 inflammasome activation impaired cell invasion and metastasis via inhibiting Akt pathway in colorectal cancer 33 . Furthermore, overexpression of AIM2 in human renal cancer suppressed cell metastasis via enhancing autophagy induction 21 .…”
Section: Discussionmentioning
confidence: 95%
“…AIM2 inflammasome activation impaired cell invasion and metastasis via inhibiting Akt pathway in colorectal cancer. 33 Furthermore, overexpression of AIM2 in human renal cancer suppressed cell metastasis via enhancing autophagy induction. 21 Our results indicated that inflammasome inhibitor YVAD-CMK resulted in the reduction of oncolytic effect by Ad-CAIX promotor -AIM2, implied that this efficiency was dependent on AIM2 inflammasome activation responses.…”
Section: Ad-caix Promotor -Aim2 Promoted the Inhibition Of Lung Metas...mentioning
confidence: 99%
“…No phosphorylation sites responsible for regulating the activity of either AIM2 or NLRP1 have been characterised, although several putative sites have been identified in high-throughput screens according to PhosphoSitePlus® [72]. Interestingly, AIM2 has inflammasome-independent roles in mouse models of colon cancer and in Experimental Autoimmune Encephalomyelitis (EAE), a mouse model of multiple sclerosis [73][74][75]. In cancerous colonic epithelial cells AIM2 binds and inactivates the kinase DNA-PK, which is needed for AKT activation and regulates colon cancer progression [73].…”
Section: Aim2 and Nlrp1mentioning
confidence: 99%
“…The absence of PI3K/Akt pathway suppression by AIM2 has been shown to decrease apoptosis in HCT116 CRC cells [ 48 ], as well as increase the capacity of stem cells to form organoids in culture [ 45 ]. However, other studies have suggested that AIM2 may regulate CRC via caspase-1-mediated induction of cell death and regulation of the epithelial-to-mesenchymal transition [ 49 , 50 ].…”
Section: Nlr Family Apoptosis Inhibitory Proteinsmentioning
confidence: 99%